PEMANFAATAN BUAH NANAS (ANANAS COMOSUS L.) DENGAN PENAMBAHAN TEPUNG TAPIOKA DALAM PEMBUATAN KERUPUK - Indah Purnama Sari; Vonny Setiaries Johan; Faizah Hamzah3 (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The purpose of this study was to get the best ratio between pineapples puree and tapioca starch in the making of crackers. The research conducted using a complately randomize  design consists of five streatments and each was repeated three times. The treatments performed were PN1 (tapioca : pineapple puree 80%:20%), PN2(tapioca : pineapple puree 70%:30%), PN3(tapioka : pineapple puree 60%:40%), PN4(tapioca : pineapple puree 50%:50%), PN5(tapioca : pineapple puree 40%:60%), The data analyzed statistically using analysis of variance (Anova) and duncan’s new multiple range test (DNMRT) at 5% level. The result showed that the ratio between tapioca and pineapple puree the affected moisture content, ash content, vitamin C content, swelling power, and sensory test. The best treatment crackers from this research was crackers PN4(50%:50%) with had moisture content 2.14% ash content 2.49%, vitamin C 15,96 mg/100 g, content 15.96 mg, swelling power 48.79%, sensory test deskription color the                                   yellow browhnis, scant of pineapple test of pineapple, and crunchy texture. A hedonic assessment overall panelis like the crtacker. Keywords :Tapioca, pineapple puree, cracker